2021
DOI: 10.3389/fonc.2021.752504
|View full text |Cite|
|
Sign up to set email alerts
|

A Recombinant Human Adenovirus Type 5 (H101) Combined With Chemotherapy for Advanced Gastric Carcinoma: A Retrospective Cohort Study

Abstract: BackgroundThis retrospective cohort study aimed to evaluate the clinical outcomes of H101 combined with chemotherapy for advanced gastric carcinoma (GC) patients.MethodsThe advanced GC patients, who were treated with H101 and/or chemotherapy, were enrolled and divided into three groups according to treatment method. The clinical characteristics of patients, clinical short-term and long-term outcomes, followed up, and complication were analyzed.ResultsA total of 95 patients (30 patients in group A were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…What also was noted, is that side effects typical for chemotherapy such as nausea, vomiting, granulocytopenia, anemia, and hair loss occurred in patients from groups B and C (with no statistically significant difference between them) and more commonly than in group A. Pyrexia was observed mostly in patients from groups A and B. The study showed that Oncorine may be a therapeutic option for patients with gastric carcinoma in combination with chemotherapy ( 66 ). In 2022 the next retrospective study was carried out on the efficacy and safety of Oncorine in 29 patients with persistent, recurrent, or metastatic gynecologic malignancies: cervical cancer (22 cases), vaginal cancer (2 cases), vulvar cancer (3 cases) and ovarian cancer (2 cases).…”
Section: Discussionmentioning
confidence: 80%
“…What also was noted, is that side effects typical for chemotherapy such as nausea, vomiting, granulocytopenia, anemia, and hair loss occurred in patients from groups B and C (with no statistically significant difference between them) and more commonly than in group A. Pyrexia was observed mostly in patients from groups A and B. The study showed that Oncorine may be a therapeutic option for patients with gastric carcinoma in combination with chemotherapy ( 66 ). In 2022 the next retrospective study was carried out on the efficacy and safety of Oncorine in 29 patients with persistent, recurrent, or metastatic gynecologic malignancies: cervical cancer (22 cases), vaginal cancer (2 cases), vulvar cancer (3 cases) and ovarian cancer (2 cases).…”
Section: Discussionmentioning
confidence: 80%
“…The first FDA- and European Medicines Agency-approved oncolytic virus, talimogene laherparepvec (T-VEC), is a modified HSV virus for the treatment of malignant melanoma that encodes GM-CSF to enhance antitumor immune responses ( 150 ). A recombinant adenovirus (Oncorine ® ) was approved by Chinese regulators as early as November 2005 for the treatment of HNC (in combination with chemotherapy) and a number of oncolytic viruses are in clinical development ( 151 , 152 ). The multifunctional properties of oncolytic viruses in tumor therapy make them highly synergistic when used in combination with other drugs ( 153 ).…”
Section: Future Immunotherapymentioning
confidence: 99%
“…Others have also shown that tumor selectivity can also be achieved by the deletion of E1B-19 kDa ( Liu et al, 2004 ). Another oAdV, H101, is similar to ONYX-015 except it carries a mutation in the E3 gene region which is associated with immune evasion ( Zhang et al, 2021 ). H101 was well tolerated and demonstrated anti-tumoral activity in patients ( Lu et al, 2004 ).…”
Section: Different Oncolytic Viruses Applied As Immunotherapeutic Age...mentioning
confidence: 99%